Self-leadership and Teacher's Innovative Work Behavior: The Mediating Roles of Self-efficacy and Optimism - Dani Rizana (UIN Raden Mas Said Surakarta, 2022)
This study aims to identify the relationship between self-leadership and innovative behavior in the workplace with self-efficacy and optimism as mediating variables. This study used a convenience sampling method involving 121 Mathematics Teachers in Kebumen District with 121 teachers as respondents. Data were analyzed using quantitatively using the Structural Equation Model (SEM) based on Partial Least Square (PLS). The results showed that self-leadership, optimism, and self-efficacy affected innovative behavior, while self-leadership affected optimism and self-efficacy. Besides, optimism and self-efficacy could mediate the relationship between self-leadership and innovative behavior.